Fracture Toughness of Various Core Build-Up Materials - E. D. Bonilla, DDS,1 G. Mardirossian, DDS,1 and A. A. Caputo, PhD2 (Blackwell Synergy, 2000)
The purpose of this investigation was to compare the fracture toughness of several core materials.